Roles of Local Information Professionals of the Thai Provincial University Libraries - Nonthacumjane, Pussadee (Knygotyra, 2021)
This paper aims to investigate the roles of information professionals in local information departments. These roles were identified by interviewing the members of the Local Information Working Group of the Provincial University Library Network (PULINET) in Thailand. This study applied qualitative research methods, including the 23 interviews of the Local Information Working Group members and a qualitative observation. The need for investigation of the roles as perceived by local information professionals was prompted by the placement of local information departments in the provincial university libraries, which is different from the Western countries where similar work is carried out in public libraries. The activity theory was applied to understand the roles of these professionals as emerging within their community through the division of labor, norms as expressed in responsibilities, and actions as expressed in functions of local information professionals. The study has revealed eight professional roles including manager, curator, service provider, promoter, researcher, collaborator, learner, and educator that overlap with the roles identified in the library research of other countries. The study included a specific group of respondents – the members of a working group of the Thai provincial university library network. This group consists of the representatives of all Thai provincial university libraries and is producing the recommendations and standards for local information work, works with competence development and develops common local information resources. Thus, the results of interviews with its members are both limited to this group, but also can be generalized to a wider professional community of provincial university librarians.
Keywords: information professionals; local information departments; Local Information Working Group; Provincial University Library Network; Thailand